Evaluation of intervertebral disc degeneration using T2 signal ratio on magnetic resonance imaging. Issue 152 (July 2022) - Kamei, Naosuke; Nakamae, Toshio; Nakanishi, Kazuyoshi; Tamura, Takayuki; Tsuchikawa, Yuji; Morisako, Taiki; Harada, Takahiro; Maruyama, Toshiaki; Adachi, Nobuo
Highlights: T2 signal ratios of the lumbar intervertebral discs and the spinal cords were used. Signal ratios reduced the discrepancy between the two MRIs of the same person. Signal ratios showed reasonable changes with age and Pfirrmann grade. Abstract: Purpose: Intervertebral disc degeneration is assessed clinically by magnetic resonance imaging (MRI). Although some quantitative evaluation methods for MRI under special imaging conditions have been reported, they are widely and generally difficult to use. The aim of this study is to determine if intervertebral disc degeneration can be assessed using the ratio of MRI T2 values of the disc to the spinal cord T2 values. Methods: Signal ratio was calculated using the T2 signal intensity of the disc and the spinal cord on MRI under common conditions for a new assessment of disc degeneration. T2-weighted images of 100 patients undergoing MRI twice within a year under different imaging conditions, 1.5 T or less and 3.0 T, were used for the assessment. The T2 signal intensity was measured at the center of the discs at L2-3, L3-4, L4-5, L5-S1 and the spinal cord at T12 level. Signal ratio was calculated using these T2 signal intensity values. The ratio of the difference between the first and second values to the mean of the first and second values was calculated to confirm the equivalence of MRI assessments of disc degeneration in the same patient under different imaging conditions. Results: The equivalence of values between the first MRI and the second MRI in the signal ratio was significantly higher than that in the T2 signal intensity. In addition, the signal ratio was negatively correlated with age and were significantly associated with Pfirrmann grade. Conclusions: By using the signal ratio, disc degeneration can be evaluated by MRI even under different imaging conditions.